The importance of trainers awarmess of the importance of diversification in training methods when developing physical qualities - MOUBIENE, Hani (Journal of Human Sciences, 2020)
This study was focused on the importance of trainers awarmess of the importance of diversification in training methods when developing physical qualities and in order to arrive to results which benefits’ our study we have divided it into two parts ;theoretical parts we reviewed the problematic , we proposed hypotheses then we specified the targets and function terms where as the practical side ,we deter med the community and sample study in addition to its verities and methodology and after analyzing and discussing the results obtained by using investigation tools which are a questionnaire and interview we came to conclude this result, the majority of trimmers unaware for the impotence of using various trimming methods to develop some physical qualities for football player.